The Effectiveness of Implementing Dzikir Therapy to Reduce Anxiety Levels in the Elderly - Refina Anggraini; Kartinah Kartinah (GLOBAL HEALTH SCIENCE GROUP, 2024)
The anxiety experienced by the elderly in Indonesia is very high. The causes of anxiety in the elderly usually include physical changes, degenerative and chronic diseases, loneliness, fear of losing freedom, fear of facing death. Some nursing management to reduce anxiety levels can be treated with pharmacological therapy such as anti-anxiety drugs (Anxiolytics) and non-pharmacological therapy such as spiritual therapy and relaxation therapy. One of the non-pharmacological therapies to relieve anxiety is to carry out dhikr therapy using dhikr readings (remembering Allah). The aim of this research is to determine the effectiveness of implementing dhikr therapy to reduce anxiety levels in the elderly at Wisma Wukiratawu. Method: The research design used by researchers is a case study. Data collection in this research was carried out through interviews and observations. The research subjects were 10 elderly people at the Tresna Werdha Abiyoso Social Home. The research was conducted at the Tresna Werdha Abiyoso Social Home in May 2024. The instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire. Results: From the pretest, the respondent's anxiety level was measured before the therapeutic intervention was carried out. Subjects were asked to fill out an anxiety scale that had been created by the researcher. Of the 10 subjects who were respondents in this study, 7 of them had moderate to severe levels of anxiety. In the posttest, the level of anxiety is measured again after the intervention is carried out. The aim of measuring anxiety levels after intervention is to determine the extent of development that has occurred after therapy. After the therapy was implemented, the majority of respondents' anxiety levels were in the mild and no anxiety category. Conclusion: Subject 10 people felt more calm and grew in self-confidence, were more enthusiastic and had more positive thoughts about themselves and others. No longer feel excessive anxiety.